Prevalence of various psychotic disorders among patients with type 2 diabetes: Real-world evidence from Shanghai, China - Yunxi Ji; Ping He; Yingxia Zhou; Huayan Yao; Yanbin Xue; Renjie Jing; Tingyu Zhang; Wen Sun; Ping Lu; Bin Cui; Weiqing Wang (Diabetes Epidemiology and Management)
Aims: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that significantly impacts psychotic health, leading to increased incidence and mortality. We aim to explore the status of patients with T2DM and the issue of comorbid psychotic disorders. Methods: Our study estimated the characteristics of 836,120 patients with T2DM from 2019 to 2023 based on electronic health records from the Shanghai Link Database (SHLD). We calculated the prevalence of the four major psychotic disorders in patients with T2DM, including depression, anxiety, dementia, and schizophrenia. The data was also stratified by age, sex, and other factors. Additionally, the association between diabetes complications and various psychotic disorders was investigated. Results: We observed that the age group of 55-80 counted for about 68.15% of the total population with T2DM. There were more male patients with T2DM than females, but females exhibited a higher overall prevalence of psychotic disorders compared to males. For patients with T2DM, anxiety had the highest prevalence (3.97%), followed by depression (2.33%), dementia (2.04%), and schizophrenia (0.16%). There was a significant relationship between psychotic disorders and various diabetes complications. Conclusions: The high prevalence of psychotic disorders among patients with T2DM highlights the importance of considering the impact of their comorbid psychotic illnesses when treating T2DM. Developing high-quality diabetes healthcare and implementing targeted treatment and management plans are essential in addressing these issues.